2016
DOI: 10.1136/bmjopen-2016-011445
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine use in Central Germany: protocol for a qualitative study exploring requirements and challenges in healthcare from the professionals' perspective

Abstract: IntroductionThe synthetic drug methamphetamine with its high addiction potential is associated with substantial adverse health effects. In Germany, especially Central Germany, the increase in the consumption of methamphetamine has exceeded that of other illegal drugs. The treatment system and service providers are facing new challenges due to this rise in consumption. This qualitative study will explore the demand created by the increasing healthcare needs of methamphetamine-addicted persons in Central Germany… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
1
7
0
3
Order By: Relevance
“…Similarly, population‐normalised DMA and MA loads did not show any weekend peak, which was commonly seen for cocaine and MDMA. This is in agreement with results from previous studies, which suggested that MA is consumed constantly across the whole week (ie, regular use not limited to nightlife) …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, population‐normalised DMA and MA loads did not show any weekend peak, which was commonly seen for cocaine and MDMA. This is in agreement with results from previous studies, which suggested that MA is consumed constantly across the whole week (ie, regular use not limited to nightlife) …”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with results from previous studies, which suggested that MA is consumed constantly across the whole week (ie, regular use not limited to nightlife). 22,33,41 Multi-year data was available for one location (ie, QLD1). Interestingly, DMA/MA ratios varied greatly between 2011 and 2013, whilst a sharp decrease was observed from 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Die Gefahren durch amphetaminartige Substanzen (ATS), insbesondere durch Methamphetamin, sind schwerwiegend, gehen mit ihrem hohen Abhängigkeitspotential doch vermehrt kardiovaskuläre und zerebrovaskuläre Erkrankungen, Infektionskrankheiten, Abszesse, Zahnschäden sowie kognitive Beeinträchtigungen, Depression und Psychosen [1][2][3][4] einher. Um diesen Begleiterkrankungen vorzubeugen, aber auch um der wachsenden Nachfrage der Betroffenen nach therapeutischen Maßnahmen [4,5] Rechnung zu tragen, gilt es, geeignete Präventions-und Interventionsmaßnahmen zu entwickeln.…”
Section: Introductionunclassified
“…Bei der Auswahl der Teilnehmer für die Fokusgruppen wurde darauf geachtet, möglichst heterogene Gruppen, d. h. Experten aus unterschiedlichen Versorgungsbereichen, zu gewinnen, um ein breites Spektrum an Expertenwissen diskutieren und reflektieren zu können. Nähere Informationen zum methodischen Vorgehen und dem Gesamtkontext der Studie sind im Studienprotokoll zu finden [31].…”
Section: Materials Und Methodenunclassified